Motivasi Dan Penggunaan Teknologi Informasi Dalam Meningkatkan Kinerja Karyawan Pada RSIA Kurnia Indah Medika Muara Enim - Eni Cahyani; agusri; Novita Sari Novita; Hertanudin Hertanudin; Darsih Darsih (DIBINOM : Digital Business, Economic Jurnal, 2026)
Background: Employee performance is critical in hospitals demanding fast, accurate services. RSIA Karunia Indah Medika Muara Enim faces suboptimal performance of non-medical staff, indicated by high absenteeism (22.61%–35.31% in 2020–2022), delayed patient services, and administrative complaints. Material motivation (allowances, bonuses) has failed to improve performance, while information technology (SIMRS) implementation remains limited and uneven. Objective: To analyze the influence of motivation (material and non-material) and information technology utilization on employee performance, and to identify inhibiting factors. Method: Qualitative case study approach. Data collection through in-depth interviews (15 participants), passive participatory observation (4 weeks), and documentation. Data analysis used Miles, Huberman & Saldaña's model with NVivo 12. Trustworthiness ensured by triangulation and member checking. Results: Material motivation was provided but non-material motivation (recognition, praise, career path) was absent, resulting in low intrinsic motivation. Discipline enforcement was inconsistent. SIMRS improved administrative speed (registration time from 6 to 2.8 minutes) and coordination, but only for direct users. Technical constraints (weak server, power outages) and lack of training hindered performance. Non-digital workers (cleaning service, security) experienced no improvement. Conclusion: Material-only motivation and uneven IT utilization without infrastructure support cannot significantly improve performance. Management needs performance-based rewards, interpersonal communication, consistent discipline, regular SIMRS training, server upgrades, and expanded IT access to all staff.